A Combined Citizen Science—Modelling Approach for NO2 Assessment in Torino Urban Agglomeration - Matteo Bo (Atmosphere, 2020)
The #CHEARIATIRA citizen science campaign was developed in February 2019 in Torino (western part of the Po Valley megacity region). The aim of the campaign was public engagement with measuring NO2 concentrations in an urban area that often exceeds air quality standards. NO2 diffusion tubes were employed by citizens under our supervision. In this paper, we present the main outcomes of a combined approach between the #CHEARIATIRA campaign and the urban dispersion model SIRANE. The results were validated against the available public Air Quality Monitoring Stations (AQMS). The citizens’ passive samplers and the modelled data show a good response in central districts both during the campaign interval and by annual projection. Traffic hotspots and sensitive receptors (schools, hospital) have high concentrations of NO2. Most of the study area (83% of the tubes) is subject to an increased risk of premature death according to epidemiological literature.